After Zagora — Andrian Colonization in the Northern Aegean: The Case of Argilos - Perreault, Jacques Y.; Bonias, Zisis (Mediterranean Archaeology: The Australian and New Zealand Journal for the Archaeology of the Mediterranean World, 2012)
For the last twenty years, a team of Greek and Canadian archaeologists have been excavating Argilos, the earliest known Greek colony in the area of the mouth of the Strymon river. An overview of research on what was one of the four colonies founded by Andrians after the abandonment of Zagora allows discussion of questions related to the origin of the settlers, the choice of location, the foundation date, and the reasons for the settlement. First occupied by Thracians, Argilos was settled by Greeks no later than the mid-7th cent. B. C. Some of these Greeks came from Andros ; however, one should not eliminate the possibility that Argilos may have been a joint venture between Andrians and Chalcidians. Cohabitation between Greeks and Thracians lasted until the mid-6th cent., when it is believed a wave of immigrants arrived, some of whom were from east Greece. Argilos remained affluent until the foundation of Amphipolis in 437, after which it suffered decline. Its capture by Philip II in 357 and the deportation of its inhabitants to Amphipolis put an end to its existence.